Removal of Phosphate from Synthetic Aqueous Solution by Adsorption with Dolomite from Padalarang - Fadjari Lucia Nugroho; Lili Mulyatna; Anggi Doli Wiranata Situmeang (Institute for Research and Community Services, Institut Teknologi Bandung, 2014)
The presence of phosphate in wastewaters can cause eutrophication of surface water bodies leading to algal-blooming in the aquatic environment and degradation of water quality. Phosphate removal from wastewaters by conventional biological treatment removes only 10-30% of the phosphate, whilst chemical treatment using precipitants such as calcium or iron salts, although effective, is expensive and produces water-rich sludge which must be further treated. Hence, phosphate removal by adsorption in the form of Ca -phosphate has been proposed as an alternative to the more traditional methods. This study investigated the feasibility of using dolomite